PENINGKATAN KAPASITAS PENDUKUNG USAHA PADA UMKM KELOMPOK USAHA KERUPUK TEMPE BUNGONG NANGGROE DI KECAMATAN SYAMTALIRA ARON KABUPATEN ACEH UTARA - Falahuddin Falahuddin; Fuadi Fuadi; Munandar Munandar; Reza Juanda; Munardi Munardi; Mohd. Heikal (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2022)
The purpose of Community Service is carried out to provide understanding and assist business actors regarding the factors supporting business activities, such as business management factors and legality so that business activities carried out are not only profit-oriented, but business activities can continue to develop in the future by paying attention to and implementing supporting factors for business activities. At the end of the program, partners are expected to be able to do, namely 1). business actors experienced a greater increase in production capacity. 2). business actors have an increased understanding of the importance of good financial bookkeeping. 3). business actors also experienced an increased understanding of the importance of labels (Halal and brands) as a marketing strategy and applying science and technology/electronic media as a means of promotion to increase sales.